CRANIOMETRICAL ANALYSIS OF CAPRA HIRACUS AND OVIS ARIES FROM PUNJAB, PAKISTAN (The Research of Medical Science Review, 2025)
There are roughly 37 goat breeds and 30 sheep breeds recognized in Pakistan. Goats (Capra circus) and sheep (Ovis aries) are two of the first hominid animals. These species thrive in diverse habitats, from temperate forests to deserts, and display different foraging behaviors; goats are browsers that prefer a variety of plants, while sheep primarily graze on grasses. Such dietary differences may influence the development and shape of their cranial structures. This study aimed to compare cranial parameters between the two species, utilizing 10 skulls five from each species collected from various regions of Punjab, Pakistan, and preserved in the Lab at the University of the Punjab Lahore (catalogued as G1- G5 for goats and S1-S5 for sheep). Using linear craniometry, 41 parameters were analyzed, and both descriptive and multivariate analyses (MANOVA) were performed to assess differences. Significant disparities were found in neurocranium breadth, skull length, nasal length, skull width, basal length, and facial width, with all these parameters being larger in sheep, except for skull base length, which was greater in goats. These cranial differences may result from anatomical variations, evolutionary lineages, hormonal influences, environmental factors, and genetic differences. This research provides essential baseline craniometric data for species, contributing valuable insights to existing literature and guiding future studies.